Early Mental Health Morbidity and Later Smoking at age 17 years - Zubrick, Stephen; Lawrence, David; Mitrou, F.; Christensen, D.; Taylor, Catherine (Cambridge University Press, 2012)
Background. We examined the relationship between the onset and pattern of childhood mental health disorders and subsequent current smoking status at age 17 years. Method. Data were from a prospective cohort study of 2868 births of which 1064 supplied information about their current smoking at 17 years of age. The association between the onset and pattern of clinically significant mental health disorders in the child and subsequent smoking at age 17 years was estimated via multivariable logistic regression. Results. Relative to 17 year olds who never had an externalizing disorder, 17-year-olds who had an externalizing disorder at age 5, 8 or 14 years were, respectively, 2.0 times [95% confidence interval (CI) 1.24–3.25], 1.9 (95% CI 1.00–3.65) or 3.9 times (95% CI 1.73–8.72) more likely to be a current smoker. Children with an ongoing pattern of externalizing disorder were 3.0 times (95% CI 1.89–4.84) more likely to be smokers at the age of 17 years and those whose mothers reported daily consumption of 6–10 cigarettes at 18 weeks’ gestation were 2.5 times (OR 2.46, 95% CI 1.26–4.83) more likely to report smoking at 17 years of age. Associations with early anxiety and depression in the child were not found. Conclusions. Current smoking in 17-year-olds may be underpinned by early emergent, and then, ongoing, externalizing disorder that commenced as young as age 5 years as well as exposure to early prenatal maternal smoking. The associations documented in adults and adolescents that link tobacco smoking and mental health are likely to be in play at these early points in development.